Vertical Assessment of Lidar Bathymetry - Leger, M.; Gong, J.; Church, I. (The International Hydrographic Review, 2019)
Validation of Airborne Light Detection And Ranging (LiDAR) Bathymetry (ALB) is necessary for the production of nautical charts to fill coastal charting gaps and to quickly and accurately measure shallow dynamic seafloors. Previous assessments concentrate on the validation of ALB data within overlapping regions of Multibeam Echo-Sounder (MBES) data. This paper presents new coverage environments to the MBES overlap validation method, and proposes an alternative method for comparison between ALB data and ENC vector information. Analysis of the validation methods favour comparisons using overlapping MBES data; however, the overlap of ALB and ENC information provides an additional assessment method with substantial overlapping regions. The ENC comparison proves to be useful at locations where MBES data is absent and in the assessment of chart adequacy.